Research Data Management Practices: Preparedness and Challenges among Librarians in Nigeria - Alex-Nmecha, Juliet C.; Onifade, Abdurrahman B. (Ghana Library Journal, 2023)
There is a global deluge in research data generation in academia and industries as a result of the proliferation of  modern information and communication technologies (ICTs). This data deluge has raised concerns that  research data  be properly managed for easy accessibility, retrieval, use, and reuse for scientific progress.  Funding agencies and  institutions have gradually set standards or requested researchers to provide necessary  data management plans for  their research. Based on these backgrounds, this study sought to investigate  research data management (RDM)  practices, the level of preparedness, and the challenges being faced by  librarians in Nigeria. The study adopted a survey  research design of quantitative methodology. Questionnaire  developed using Google Forms and administered  electronically on LIS platforms, was used for data collection  from librarians across the six geopolitical zones in Nigeria.  The data collected was presented in charts and  analysed descriptively. Findings from the study show that lack there is a  lack of awareness about RDM policy,  and skills to organise research data among librarians. The study recommends the  formulation of comprehensive  RDM policies, awareness campaigns, and professional development initiatives to address  these challenges,  fostering a culture of effective RDM in Nigeria.